Meningkatkan Kualitas Diri dengan Berpikir Positif: Sebuah Pendekatan Stoik - Kusumaningsih, Rila (Jurnal Ilmu Sosial dan Humaniora, 2025)
Self-quality has become an important issue in modern life, full of demands and complexities. One important aspect of developing self-quality is changing the way of thinking to be more positive. Positive and constructive thinking patterns can help individuals in facing various obstacles, making the right decisions, and achieve their goals. One approach that can help in developing positive thinking patterns is the core philosophy or Stoicism. Stoicism offers valuable guidance in improving positive thinking patterns and self-quality by living in harmony with nature, using reason, and living together with others in a good and reasonable manner. This study aims to explore the importance of improving positive thinking patterns and self-quality by applying the principles of the core philosophy. This research method uses a qualitative approach with text and comparative analysis. The results of this study indicate that by understanding and applying the principles of Stoicism, one can manage negative emotions, improve positive thinking patterns, and enhance self-quality. Thus, it is important to understand and apply the principles of Stoicism in daily life to achieve happiness and a better quality of life.